STUDIES ON PLANT SUCCESSION IN SEHIMA-DICHANTHIUM GRASS COVER - Shanker, Vnid; Kanodia, K C; Dabadghao, P M (Annals of Arid Zone, 2016)
A study of plant succession was taken up at the Central Research Farm of the Indian Grassland and Fodder Research Institute, Jhansi, U. P. Grasslands of Jhansi represent Sehima-Diehanthium cover. An exposed rock outcrop was exclosed with a rodent-proof fencing. The crevices and basal areas of the outcrop have been in different phases of development and thus provided an ideal site for the study of plant succession. On the basis of the study of the primary plant succession on and round the exposed rock outcrop it has been possible to delineate pattern of primary plant succession in the Sehima-Viehanthium grass cover on the rocky substratum and red _ gravelly soil. The pace of succession in the former is slow and the successional pattern is elaborate while in the latter the pace is comparatively fast and the pattern a telescoped one.